The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1128/iai.00242-21
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae TolC Is Required for Expression of the ToxR Regulon

Abstract: Vibrio cholerae is a Gram-negative bacterium that causes the enteric disease cholera. V. cholerae colonization of the human intestine is dependent on the expression of both virulence genes and environmental adaptation genes involved in antimicrobial resistance. The expression of virulence genes, including the genes encoding for the main virulence factors cholera toxin (CT) and the toxin coregulated pilus (TCP), are coordinately regulated by the ToxR regulon. Tripartite trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…For example, secretion system related genes secA, secD , secF, yajC, yidC and tolC , which prior to studies reported that secretion system genes played roles in the bacterial adhesion, thereby promoting the adhesion of V. alginolyticus to the host surface and causing bacterial infection ( 46 ). In Vibrio cholerae , the outer membrane protein TolC is necessary for the expression of toxR regulon and participates in an efflux dependent feedback loop to regulate the expression of virulence genes, MARTX toxin secretion and resistance to antimicrobial compounds present in the host ( 47 ). In this study, we also found that ToxR protein, a key transcription activator, is acetylated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, secretion system related genes secA, secD , secF, yajC, yidC and tolC , which prior to studies reported that secretion system genes played roles in the bacterial adhesion, thereby promoting the adhesion of V. alginolyticus to the host surface and causing bacterial infection ( 46 ). In Vibrio cholerae , the outer membrane protein TolC is necessary for the expression of toxR regulon and participates in an efflux dependent feedback loop to regulate the expression of virulence genes, MARTX toxin secretion and resistance to antimicrobial compounds present in the host ( 47 ). In this study, we also found that ToxR protein, a key transcription activator, is acetylated.…”
Section: Discussionmentioning
confidence: 99%
“…The tolC (VC2436) coding sequence is encoded as a single, self-standing gene on the large chromosome ( Bina and Mekalanos, 2001 ). TolC’s RND pore function was inferred from experiments showing that a tolC deletion mutant exhibited the same antimicrobial resistance and virulence factor production phenotypes as an otherwise isogenic RND efflux pump negative strain that retains tolC ( Bina and Mekalanos, 2001 ; Weng et al., 2021 ). VexR, a transcriptional regulator belonging to the TetR family has been reported to positively regulate the expression of the vexRAB operon ( Bina et al., 2008 ; Taylor et al., 2015 ), while BreR, another member of the TetR family is a transcriptional regulator that represses vexCD expression ( Cerda-Maira et al., 2008 ; Cerda-Maira et al., 2013 ).…”
Section: Rnd Efflux Systems In V Cholerae Are Stru...mentioning
confidence: 99%
“…V. cholerae lacking RND efflux systems exhibits severe attenuation in infant mouse colonization which was hypothesized to result from an abundance of antimicrobial compounds in the gastrointestinal tract ( Bina et al., 2008 ). RND-mediated efflux together with outer membrane selective permeability is hypothesized to synergistically allow bacteria to overcome the cytotoxic effect of bile acids, detergents and antimicrobial peptides commonly found in the intestine ( Bina and Mekalanos, 2001 ; Bina et al., 2008 ; Weng et al., 2021 ). Competitive index experiments in which strains are compared pairwise for infant mouse colonization revealed that the vexBDH , vexBDK and RND null mutants could not be recovered from infant mice when administered at a 1:1 ratio with WT.…”
Section: Rnd Efflux Contributes To V Cholerae Host...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the RND efflux pumps of E. coli could not function with the TolC from V. parahaemolyticus, suggesting a species-specific preference for the TolC component [71,72]. TolC in the V. cholerae O1 El Tor strain has been reported to play an essential role in the transcription of the ToxR regulon, a finding that emphasizes the importance of efflux pump-mediated regulation of virulence in pathogenic bacteria [73].…”
Section: Efflux Pumps Of Rnd Family In Vibrio Speciesmentioning
confidence: 99%